2011
DOI: 10.1063/1.3583666
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for an angular dependent transition of magnetization reversal modes in magnetic nanotubes

Abstract: We report on the experimental and theoretical investigation of the magnetization reversal in magnetic nanotubes that have been synthesized by a combination of glancing angle and atomic layer deposition. Using superconducting quantum interference device magnetometry the angular dependence of the coercive fields is determined and reveals a nonmonotonic behavior. Analytical calculations predict the crossover between two magnetization reversal modes, namely, the movement of different types of domain boundaries (vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 34 publications
4
52
0
Order By: Relevance
“…The unintentional roughness of real nanotubes might be relevant here. In an experiment performed on a large ensemble of nanotubes, one would not have been able to judge whether a gradual decrease in MðHÞ [17] originated from a very broad switching field distribution or from the gradual tilting of magnetic moments in the individual nanotubes. Thus, our combination of nanomagnetometry techniques represents a powerful method for unraveling hidden aspects of nanoscale reversal processes.…”
Section: Prl 111 067202 (2013) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
See 1 more Smart Citation
“…The unintentional roughness of real nanotubes might be relevant here. In an experiment performed on a large ensemble of nanotubes, one would not have been able to judge whether a gradual decrease in MðHÞ [17] originated from a very broad switching field distribution or from the gradual tilting of magnetic moments in the individual nanotubes. Thus, our combination of nanomagnetometry techniques represents a powerful method for unraveling hidden aspects of nanoscale reversal processes.…”
Section: Prl 111 067202 (2013) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Because of their inherently small magnetic moment, experimental investigations have often been conducted on large ensembles. The results, however, are difficult to interpret due to stray-field interactions and the distribution in size and orientation of the individual nanotubes [12,[14][15][16][17][18]. In a pioneering work, Wernsdorfer et al [19] investigated the magnetic reversal of an individual Ni nanowire at 4 K using a miniaturized SQUID.…”
mentioning
confidence: 99%
“…Previous works reported analytical calculations of the magnetic reversal modes [coherent (C) magnetization rotation, and transverse (T) and vortex-like (V) domain walls] that are energetically more favorable for high aspect ratio NWs and NTs. 8,[13][14][15]20,27,[38][39][40] For analytical calculations it is important to define the parameter b ¼ d i =d, where d i and d are the NT inner and outer diameters, respectively, (Fig. 5).…”
Section: B Magnetization Reversalmentioning
confidence: 99%
“…It has been shown that atomic layer deposition (ALD) is an excellent technique to conformally coat complex nanostructures and sculptured thin films. 4,5 In general, the characterization of material properties and quantification of material fractions of complex anisotropic thin films is a challenge. Non-destructive optical investigations, in particular, generalized ellipsometry is an excellent technique for probing anisotropic physical properties.…”
mentioning
confidence: 99%